Differences in Virus-Induced Cell Morphology and in Virus Maturation between MVA and Other Strains (WR, Ankara, and NYCBH) of Vaccinia Virus in Infected Human Cells - Gallego-Gómez, Juan Carlos (American Society for Microbiology, 2003)
Live recombinants based on attenuated modified vaccinia virus Ankara (MVA) are potential vaccine candidates against a broad spectrum of diseases and tumors. To better understand the efficacy of MVA as a human vaccine, we analyzed by confocal and electron microscopy approaches MVA-induced morphological changes and morphogenetic stages during infection of human HeLa cells in comparison to other strains of vaccinia virus (VV): the wild-type Western Reserve (WR), Ankara, and the New York City Board of Health (NYCBH) strains. Confocal microscopy studies revealed that MVA infection alters the cytoskeleton producing elongated cells (bipolar), which do not form the characteristic actin tails. Few virions are detected in the projections connecting neighboring cells. In contrast, cells infected with the WR, Ankara, and NYCBH strains exhibit a stellated (multipolar) or rounded morphology with actin tails. A detailed transmission electron microscopy analysis of HeLa cells infected with MVA showed important differences in fine ultrastructure and amounts of the viral intermediates compared to cells infected with the other VV strains. In HeLa cells infected with MVA, the most abundant viral forms are intracellular immature virus, with few intermediates reaching the intracellular mature virus (IMV) form, at various stages of maturation, which exhibit a more rounded shape than IMVs from cells infected with the other VV strains. The “IMVs” from MVA-infected cells have an abnormal internal structure (“atypical” viruses) with potential alterations in the core-envelope interactions and are unable to significantly acquire the additional double envelope to render intracellular envelope virus. The presence of potential cell-associated envelope virus is very scarce. Our findings revealed that MVA in human cells promotes characteristic morphological changes to the cells and is able to reach the IMV stage, but these virions were not structurally normal and the subsequent steps in the morphogenetic pathway are blocked.